2023
DOI: 10.3389/fnagi.2023.1069155
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion improves hypothalamus Aqp4 polarization in APP/PS1 mice: Evidence from spatial transcriptomics

Abstract: Aquaporin-4 (AQP4) is highly polarized to perivascular astrocytic endfeet. Loss of AQP4 polarization is associated with many diseases. In Alzheimer’s disease (AD), AQP4 loses its normal location and thus reduces the clearance of amyloid-β plaques and tau protein. Clinical and experimental studies showed that moxibustion can improve the learning and memory abilities of AD. To explore whether moxibustion can affect the polarization of AQP4 around the blood-brain barrier (BBB), we used spatial transcriptomics (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Electroacupuncture treatment reduced Aβ level, enhanced perivascular in ux in the GS, inhibited astrocyte reactivity, and improved AQP4 polarity in the SAMP8 mouse model of AD [54]. In addition, moxibustion increased the polarization of hypothalamic AQP4 and ameliorated cognitive impairment in APP/PS1 mice [55]. Therefore, the current authors speculate that acupuncture can promote cognitive function through glymphatic-uid transport by reducing Aβ accumulation and through an interesting therapeutic target of AQP4.…”
Section: Future and Prospects Of Gs In Cognitionmentioning
confidence: 68%
“…Electroacupuncture treatment reduced Aβ level, enhanced perivascular in ux in the GS, inhibited astrocyte reactivity, and improved AQP4 polarity in the SAMP8 mouse model of AD [54]. In addition, moxibustion increased the polarization of hypothalamic AQP4 and ameliorated cognitive impairment in APP/PS1 mice [55]. Therefore, the current authors speculate that acupuncture can promote cognitive function through glymphatic-uid transport by reducing Aβ accumulation and through an interesting therapeutic target of AQP4.…”
Section: Future and Prospects Of Gs In Cognitionmentioning
confidence: 68%
“…In addition, it has been reported that the localization of AQP4 also depends on the correct organization of the astrocytic endfeet, which, in turn, depends on the assembly of the gap junctions (GJs), formed by connexins 43 and 30 (Cx43 and Cx30, respectively), between the endfeet; microhemorrhages are indeed more frequent in C43-deficient mice [7]. Actually, brain edema has been evidenced in many pathological conditions, from cancer to stroke, and, in many cases, altered production and/or localization of AQP4 has been found, while, at the same time, the involvement of AQP4 in all these alterations suggests this protein and its organization as a therapeutic target [75][76][77][78][79]. Recently, an AQP4 variant with a C-terminal extension (AQP4x) has been also isolated, and it has been shown that it plays a role in BBB integrity [80].…”
Section: Astrocytes and Bbb Formation And Maintenancementioning
confidence: 99%
“…Current research has established that diminished AQP4 expression leads to reduced Aβ clearance and causes Aβ accumulation, leading to deficiencies in memory and learning ability and the development of CI ( Hubbard et al, 2018 ; Chandra et al, 2021 ; Fang et al, 2021 ; Liu et al, 2022 ; Wang et al, 2022 ; Vasciaveo et al, 2023 ). In addition to regulating water homeostasis, AQP4 also activates astrocytes ( Yang et al, 2022 ; Liu et al, 2023 ), and outside of the brain, it is expressed by IHCs ( Christensen et al, 2009 ; Nishio et al, 2013 ). AQP4 is now widely believed to be involved in maintaining the osmotic balance during the K + cycle as well as the ionic balance of the endolymphatic fluid ( Li and Verkman, 2001 ; Mhatre et al, 2002 ).…”
Section: Co-morbidity Hypothesismentioning
confidence: 99%